Email-Based Nudges and Guideline-Concordant Statin Prescribing in a Federally Qualified Health Center Network: A Prospective Quality Improvement Initiative - David Golombeck; Nicholas Illenberger; Chase McCaleb; Isaac Dapkins; Antoinette Schoenthaler; George Shahin; Judd Anderman; Doreen Colella; Arielle Elmaleh-Sachs (Journal of Primary Care & Community Health, 2026)
Objectives This quality improvement project evaluated trends in guideline-concordant statin prescription rates during implementation of an email-based nudge intervention among healthcare providers at a large FQHC network. Methods Eligible encounters included patients meeting UDS guideline criteria but not receiving treatment. On the morning of each eligible visit, providers received an email nudge. Providers were categorized as early adopters or non–early adopters, with early adopters defined as opening >50% of emails during this period. Outcomes included provider-level prescribing rates, and encounter-level prescribing stratified by email engagement. This study was designed, conducted, and reported in accordance with SQUIRE 2.0 guidelines. Results Seventy-five providers who received ≥5 nudges within the first three months were included in the early adopter analysis, and a total of 124 providers with 1,236 unique patient encounters were analyzed over 12 months for encounter-level prescribing rates. Guideline-concordant statin prescribing was modestly higher over time in both groups (early adopters: 85.6% to 89.2%, p < 0.001; non–early adopters: 83.3% to 89.4%, p < 0.001), with no significant evidence of differences between groups over the 1-year period (p = 0.734). At the encounter level, while successful prescribing occurred in 21.8% of visits when the email was opened prior to the encounter compared with 19.5% when it was not opened, this difference was not statistically significant (p = 0.442). Conclusion Guideline-concordant statin prescribing was modestly higher over the study period, though no differential association by email engagement was observed. Given that email nudges are scalable and low-cost, they have the potential to serve as useful adjunctive tools, however further research is needed in settings lacking EHR-integrated alerts or with lower baseline adherence.